Comparison of Shear Bond Strength, Adhesive Remnant Index and Enamel Cracks in Bonding and Rebonding of Stainless Steel Brackets to Enamel Surface Conditioned with Er:YAG Laser Versus Conventional Acid Etching - Elahe Soltanmohamadi Borujeni; Javad Chalipa; Ardavan Etemadi; Maryam Nasiri; Mohammad Javad Kharrazifard; Mohammad Sadegh Ahmad Akhoundi (Tehran University of Medical Sciences, 2021)
Objectives: The aim of the present study was to compare shear bond strength (SBS), adhesive remnant index and enamel cracks in bonding and rebonding of brackets to enamel, conditioned with erbium-doped yttrium aluminium garnet (Er:YAG) laser and conventional acid-etching. Materials and Methods: Fifty-two bovine lower incisors were randomly divided into four groups consisting of group 1 (acid-conditioning in both bondings), group 2 (acid-conditioning in first and laser-conditioning in second bonding), group 3 (laser-conditioning in first- and acid-conditioning in second bonding), and group 4 (laser-conditioning in both bondings). After bracket placement, the samples were thermocycled and tested for SBS in both bonding procedures. Adhesive remnant index scores and enamel cracks were also determined. Tukey's test and one-way analysis of variance was used for statistical analysis (P<0.05). Results: Mean SBS in the first bonding was 23.59MPa in groups 1 and 2, and 6.9MPa in groups 3 and 4. (P<0.001). The acid-etched teeth had a significantly lower SBS in rebonding, regardless of the reconditioning method (P<0.001). The SBS of the teeth conditioned with Er:YAG laser in the first bonding did not show significant changes in rebonding, although mean SBS was higher compared to the first bonding (P=0.675). Bonding most often failed at the enamel-adhesive interface and enamel cracks were observed in a few teeth. Conclusion: The method of primary enamel preparation can affect SBS in rebonding. Based on our results, the mean SBS of Er:YAG-conditioned groups was clinically acceptable in bonding and rebonding, although it was lower compared to the acid-etched samples.